Small-Signal Distributed Frequency Modeling and Analysis for Grid-Forming Inverter-Based Power Systems - Qi, Xiaojing; Zheng, Jianyong; Mei, Fei (Frontiers in Energy Research, 2022)
More and more renewable energy sources are integrated into power grid leading to a power electronic based low inertia system. The grid-forming (GFM) inverter is an effective method to improve the inertia of the system. However, with the increased GFM inverters in the system, how the multiple control parameters affect the frequency response is still not clear. In this paper, first, a small-signal model for the GFM inverter based power system is established for distributed frequency response analysis. Based on the proposed model, the influence of the multiple parameters to the frequency response is analyzed. It is concluded that both the inertia and damping coefficient affect the settling time, overshoot and oscillation of the frequency. Finally, the simulation results verify the proposed model and the conclusion.